Implementation of a Cloud-Based CRM System to Improve Customer Loyalty in Digital Startups in Indonesia - Purwanto, Agus; Nugroho, Anggun; Bahy, Lanang Mustika; Santoso, Joko; Hanief, Shofwan (West Science Information System and Technology, 2025)
The rapid growth of digital startups in Indonesia has created a highly competitive market where customer loyalty is critical for long-term sustainability. This study explores the implementation of cloud-based Customer Relationship Management (CRM) systems as a strategic tool to enhance customer loyalty in digital startups. Using a qualitative research approach, data were collected through semi-structured interviews with five informants, including founders, managers, and IT specialists from startups in the e-commerce, fintech, and digital services sectors. The findings reveal that cloud-based CRM systems provide significant benefits, including improved customer engagement, real-time responsiveness, personalized communication, and scalability to support business growth. However, the study also identifies challenges related to data security, staff readiness, and system integration. The results highlight that cloud-based CRM is not only a technological tool but also a strategic enabler that helps startups build competitive advantage through customer-centric approaches. This research contributes to the understanding of CRM adoption in emerging markets, offering practical insights for digital entrepreneurs in Indonesia to strengthen customer loyalty.